Answer:
Solution is [tex]y=c_{1}e^{2x}+c_{2}e^{-2x}+\frac{1}{4}xe^{2x}[/tex]
Step-by-step explanation:
the given equation y''-4y[tex]=e^{2x}[/tex] can be written as
[tex]D^{2}y-4y=e^{2x}\\\\(D^{2}-4)y=e^{2x}\\\\[/tex]
The Complementary function thus becomes
y=c_{1}e^{m_{1}x}+c_{2}e^{m_{2}x}
where [tex]m_{1} , m_{2}[/tex] are the roots of the [tex]D^{2}-4[/tex]
The roots of [tex]D^{2}-4[/tex] are +2,-2 Thus the comlementary function becomes
[tex]y=c_{1}e^{2x}+c_{2}e^{-2x}[/tex]
here [tex]c_{1},c_{2}[/tex] are arbitary constants
Now the Particular Integral becomes using standard formula
[tex]y=\frac{e^{ax}}{f(D)}\\\\y=\frac{e^{ax}}{f(a)} (f(a)\neq 0)\\\\y=x\frac{e^{ax}}{f'(a)}(f(a)=0)[/tex]
[tex]y=\frac{e^{2x}}{D^{2}-4}\\\\y=\frac{e^{2x}}{(D+2)(D-2)}\\\\y=\frac{1}{D-2}\times \frac{e^{2x}}{2+2}\\\\y=\frac{1}{4}\times \frac{e^{2x}}{D-2}\\\\y=\frac{1}{4}xe^{2x}[/tex]
Hence the solution is = Complementary function + Particular Integral
Thus Solution becomes [tex]y=c_{1}e^{2x}+c_{2}e^{-2x}+\frac{1}{4}xe^{2x}[/tex]